2022
DOI: 10.1111/cas.15279
|View full text |Cite
|
Sign up to set email alerts
|

Cancer metabolism challenges genomic instability and clonal evolution as therapeutic targets

Abstract: Although cancer precision medicine has improved diagnosis and therapy, refractory cancers such as pancreatic cancer remain to be challenging targets. Clinical sequencing has identified the significant alterations in driver genes and traced their clonal evolutions. Recent studies indicated that the tumor microenvironment elicits altera-How to cite this article: Takeda Y, Chijimatsu R, Ofusa K, et al. Cancer metabolism challenges genomic instability and clonal evolution as therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…To understand the mechanism and facilitate further study on PDAC, this review article focused on the various critical alterations that occur in PDAC at the RNA, proteins, and metabolite level associated with genetic alterations of PDAC. We propose that profiling of RNA modifications will be helpful for a precise diagnosis in the early stages of PDAC [ 8 ] to allow therapeutic interventions and potentially increase patient survival rate [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the mechanism and facilitate further study on PDAC, this review article focused on the various critical alterations that occur in PDAC at the RNA, proteins, and metabolite level associated with genetic alterations of PDAC. We propose that profiling of RNA modifications will be helpful for a precise diagnosis in the early stages of PDAC [ 8 ] to allow therapeutic interventions and potentially increase patient survival rate [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies suggested that RNA methylation contributed to PDAC and other elements of tumor heterogeneity(25). RNA modification reportedly exerted a critical function in transcriptional regulation(25), translational regulation(25), A-to-I editing(89), chemoradiation therapy resistance(53,77), miRNA and ncRNA signaling(90), metabolic dependencies(91), and epigenetic regulation(92). These mechanisms are responsible for the orchestration of the control of proliferation, migration, and angiogenesis of CSC-like cells, for stem cell maintenance and differentiation, as well as for evasion of antitumor immunogenic cells(93).…”
mentioning
confidence: 99%